Koto dalam Toponimi: Nilai-nilai Sosial Budaya dalam Nama-nama Nagari Minangkabau di Sumatera Barat - Fajria, Ranti; Arimi, Sailal (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This study examines the use of 'koto' (meaning 'city') in 107 village (nagari) names in West Sumatra, Indonesia, analyzing naming patterns, interpreting meanings, and exploring their connections to Minangkabau socio-cultural values. Data collected from the official website of West Sumatra's Badan Pusat Statistik reveal three key findings: four naming patterns ((head+modifier), (modifier+head+modifier), (modifier+head), and mixed pattern), eight semantic categories (spatial, temporal, personal names, plants, landforms, numerals, animals, and tools), and reflected socio-cultural values (communal nature, agrarian roots, and the philosophy of 'alam takambang jadi guru' or 'nature is a teacher'). The toponymy of Indonesian place names often incorporates elements meaning 'city,' such as 'kutha' in Javanese and 'kute' in Balinese and Acehnese, with 'koto' being prominent in Minangkabau. This research contributes to the preservation of intangible cultural heritage by documenting toponymic traditions for future generations of the Minangkabau community, offering insights into their linguistic practices and cultural values as reflected in place names.